A functional material based on ester group structure, a preparation method and application thereof in treating perfluoro and polyfluoro alkyl substances in wastewater
Patent Information
- Application Number
- CN202511420547.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-30
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-09-30
AI Technical Summary
针对现有吸附剂在低pH值下的酸性工业废水中捕获PFOA时,PFOA分子形态阻碍离子交换作用,进而影响捕获效果的问题,
一、基于酯基结构的功能材料:
Smart Images

Figure CN121222404B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of adsorption materials technology, and more specifically, relates to a functional material based on an ester structure, its preparation method, and its application in treating perfluorinated and polyfluoroalkyl substances in wastewater. Background Technology
[0002] Per- and polyfluoroalkyl substances (PFAS) are a class of organic compounds primarily composed of carbon and fluorine atoms. They are widely used in industrial production and consumer goods. PFAS include perfluorosulfonic acids and perfluorocarboxylic acids, such as perfluorooctanoic acid (PFOA), perfluorononanoic acid, and perfluorohexanesulfonic acid. Due to their unique chemical structure, PFAS exhibit high stability and surface activity, remaining stable under high temperatures, light, chemical, or microbial conditions. They are among the most recalcitrant organic pollutants discovered worldwide, and their high bioaccumulation capacity poses a serious threat to human health. Therefore, it is necessary to employ appropriate treatment methods to effectively remove PFAS from water bodies and other environments, reducing their impact on the environment and human health.
[0003] Typical perfluorinated and polyfluoroalkyl substances include perfluorooctanoic acid (PFOA). Current methods for treating PFOA include photochemical methods, activated carbon adsorption, and ion exchange resin treatment. Photochemical methods have slow reaction rates and low degradation efficiency; activated carbon adsorption can adsorb PFOA in wastewater, but its adsorption efficiency is low, and the cost of treating the activated carbon after use is high. Ion exchange resin treatment utilizes ion exchange resins to remove PFAS from water. For example, a journal article (Pilot-scale removal of PFAS from chromium-plating wastewater by anion exchange resin and activated carbon: Adsorption difference between PFOS and 6:2 fluorotelomer sulfonate. Chemical Engineering Journal, 2024, Volume 481, 148569.) discloses the adsorption and removal of PFAS using anion exchange resins, showing good adsorption effects on perfluorosulfonic acid pollutants. Ion exchange resins remove PFOA from water by adsorbing it through ion exchange. However, the PFOA exchange capacity of ion exchange resins depends on the ion exchange groups, and the desorption and regeneration of the resin requires the use of salts or organic reagents, which can lead to secondary pollution problems.
[0004] In addition, in real-world scenarios, the main source of PFAS (including PFOA) is metal plating wastewater (Qu, YX et al. Occurrence, removal and emission of per- and polyfluorinated alkylsubstances (PFASs) from chrome plating industry: A case study in Southeast China). Emerg. Contam. 6, 376–384 (2020)., with a pH of 1–2, the degradation of PFOA using ion exchange resins faces a double dilemma: (i) at low pH values, the molecular form of PFOA (pKa approximately 3.8) hinders ion exchange, therefore, chemical reagents are needed to adjust the pH to neutral in order to effectively utilize the mechanism of ion exchange resins to capture PFOA. However, this process generates high-salt wastewater and leads to energy consumption; (ii) the regeneration process of ion exchange resins depends on high-concentration salt solutions or organic solvents, which not only leads to high economic costs but also causes secondary pollution.
[0005] Therefore, researchers must re-examine the design of adsorbents and develop new adsorbents to meet the requirements of acidic environments and achieve efficient capture and green regeneration. Summary of the Invention
[0006] 1. The problem to be solved To address the issue that the molecular structure of PFOA hinders ion exchange and thus affects the capture efficiency of existing adsorbents in acidic industrial wastewater at low pH values, this paper discusses the problem of existing adsorbents capturing PFOA. The primary objective of this invention is to provide a functional material based on an ester structure that can achieve efficient adsorption and separation of PFOA; A second objective of this invention is to provide a method for preparing the above-mentioned functional materials based on ester group structures; A third objective of this invention is to provide applications of the above-mentioned functional materials based on ester structures.
[0007] 2. Technical Solution To solve the above problems, the technical solution adopted by the present invention is as follows: The first aspect of this invention provides a functional material based on an ester group structure, which is applied to the adsorption of PFOA, and the functional material satisfies the following: (i) The functional material has a hydrophobic alkyl chain and a functional group containing an ester structure; the adsorption energy between the functional group and PFOA is... 14.6 kcal / mol to 10.2 kcal / mol, preferably, the adsorption energy with PFOA is 14.6 kcal / mol to 10.2 kcal / mol; (ii) The ratio of the pore size of the functional material to the size of the PFOA is 2:1 to 8:1, preferably 4:1; (iii) The difference in adsorption energy between acidic and neutral environments satisfies the following condition: the adsorption energy in the acidic environment is... Adsorption energy ranges from 4500.5 kcal / mol to -4000.2 kcal / mol in neutral environments, with an adsorption energy of -1000.8 kcal / mol to The adsorption energy is 900.7 kcal / mol, and the difference between the adsorption energies in neutral and acidic environments is 2999.4~3599.8 kcal / mol.
[0008] Based on the hydrophilic site of -COOH and the hydrophobic properties of the fluorocarbon chain in the typical perfluorooctanoic acid (PFOA) molecule of PFAS, this application innovatively proposes multiple possible interaction mechanisms between PFOA and the designed materials: (i) electrostatic attraction between -COOH and -CO-O- in PFOA; (ii) hydrophobic interaction between the fluorocarbon chain and the polymer backbone; (iii) intermolecular hydrogen bonding; and (iv) molecular sieve effect between the adsorbent pore size and the pollutant. Density functional theory (DFT) and molecular dynamics simulation (MD) systems are used to calculate the possible interaction forces between these two mechanisms, thereby quantitatively analyzing the priority of these interactions and guiding the design and synthesis of the materials.
[0009] Specifically, based on density functional theory (DFT), the thermodynamic parameters between different functional groups and PFOA are compared, and an adsorbent material with the optimal functional unit is designed. Based on the design of functional basic units, a series of materials with gradient pore size distribution were constructed, and the influence of pore size on PFOA trapping performance was studied by molecular dynamics (MD) simulation. By comparing the differences in the adsorption thermodynamic parameters of materials in acidic and neutral environments, guidance can be provided for the green regeneration design of materials.
[0010] According to any embodiment of the first aspect of the present invention, the functional material based on an ester group structure comprises the following structure:
[0011] The functional material comprises repeating units formed by linking methyl methacrylate and a crosslinking agent; the crosslinking agent includes one or both of ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate.
[0012] According to any embodiment of the first aspect of the present invention, the functional material based on an ester structure has pores on its surface, the average pore size of the functional material is 2-10 mm, preferably 4-5 nm, and more preferably the pore size is concentrated in the range of 3-5 nm, and the specific surface area is 440.5-510.5 m². 2 / g.
[0013] The concentrated distribution is based on BET detection data, where the concentrated peak distribution of pore size is between 3 and 5 nm.
[0014] Preferably, the pore size of the functional material based on the ester structure is concentrated in the range of 3.8~4.3 nm.
[0015] It should be noted that the concentrated pore size distribution of the functional material based on the ester group structure is between 3 and 5 nm, and there is a pore adaptation effect, which allows PFAS with molecular size between 1 and 2 nm to be adsorbed on the functional material. If the pore size is too small, it will restrict the entry of PFOA, so that PFOA cannot enter the pore and is repelled, resulting in no adsorption. If the pore size is too large, the adsorption effect is not ideal and the efficiency is low.
[0016] A second aspect of the present invention provides a method for preparing the above-mentioned functional materials based on ester group structures. It includes raw materials: monomers, crosslinking agents, pore-forming agents, and initiators; The process includes the following steps: polymerizing monomers, crosslinking agents, porogens, and a medium containing a dispersant under the action of an initiator to obtain the novel functional material based on the ester structure; The monomer is methyl methacrylate; The crosslinking agent includes one or two of trimethylolpropane trimethacrylate and ethylene glycol dimethacrylate. The applicant starts from the perspective of the charge regulation effect between monomers and crosslinking agents and PFOA. The charge regulation effect refers to the electrostatic attraction caused by the difference between positive and negative charges between the material and the pollutant. By utilizing the electrostatic attraction caused by the charge difference between the material and the pollutant, the charge regulation effect is driven, and monomers and crosslinking agents are selected in a targeted manner to prepare novel functional materials with good adsorption and separation effect of PFOA.
[0017] The porogen is dodecylbenzene; using dodecylbenzene as a porogen causes the pore size of the ester-based functional material to be concentrated in the range of 3-5 nm.
[0018] According to any embodiment of the second aspect of the present invention, the initiator includes one or more of benzoyl peroxide and azobisisobutyronitrile.
[0019] The dispersant includes hydroxyethyl cellulose; The medium is preferably an aqueous phase.
[0020] The preparation method according to any embodiment of the second aspect of the present invention specifically includes the following steps: S1. Under continuous stirring, a pore-forming agent and an initiator are added to the monomer and crosslinking agent; S2. Add the mixture obtained in step S1 to a medium containing a dispersant, carry out a constant-temperature polymerization reaction, and keep it at the temperature to obtain the functional material based on the ester structure.
[0021] According to any embodiment of the preparation method of the second aspect of the present invention, in step S1, the weight ratio of the monomer to the crosslinking agent is 1:2 to 1:8.
[0022] According to any embodiment of the preparation method of the second aspect of the present invention, the weight ratio of the porogen to the monomer and the crosslinking agent is 1:3 to 1:10.
[0023] It should be noted that the weight ratio of the porogen to the monomer and crosslinking agent reactant refers to the weight of the porogen / (the sum of the weights of the monomer and crosslinking agent).
[0024] According to any embodiment of the second aspect of the present invention, the weight ratio of the initiator to the monomer and the crosslinking agent is 1:100 to 6:100.
[0025] It should be noted that the weight ratio of the initiator to the monomer and crosslinking agent reactants refers to the weight of the initiator divided by the sum of the weights of the monomer and the crosslinking agent.
[0026] Preferably, the initiator is benzoyl peroxide.
[0027] According to any embodiment of the second aspect of the present invention, in step S2, the weight ratio of the dispersant to the medium in the medium is 0.5:1000 to 5:1000.
[0028] Preferably, the medium is water and the dispersant is hydroxyethyl cellulose.
[0029] According to any embodiment of the second aspect of the present invention, the weight ratio of the medium containing the dispersant to the reactants is 1:1 to 8:1. The reactants include monomers and crosslinking agents.
[0030] Furthermore, in step S2, before the polymerization reaction, a protective gas is introduced to remove oxygen and prevent oxidation of the monomers and crosslinking agents.
[0031] For example, the polymerization reaction can be carried out in a nitrogen atmosphere, or in an inert gas such as helium or argon.
[0032] For example, the duration of nitrogen gas introduction is 20-30 minutes.
[0033] According to any embodiment of the second aspect of the present invention, in the preparation method, in step S2, the stirring speed is 250~350 rpm.
[0034] According to the preparation method of any embodiment of the second aspect of the present invention, the polymerization reaction is carried out at a temperature of 80-90°C for a time of 6-10 hours. The polymerization reaction time affects the number of repeating units in the functional material, ultimately affecting the structure of the functional material.
[0035] According to any embodiment of the second aspect of the present invention, the heat preservation temperature is 85~95℃ and the time is 8~12h, during which the resin is cured, thereby increasing the mechanical strength of the material.
[0036] According to any embodiment of the second aspect of the present invention, the preparation method is followed by cooling after the heat preservation step to obtain a functional material based on an ester structure, and further includes extraction and purification of the novel functional material based on the ester structure.
[0037] The eluent used for extraction is acetone, but methanol, low-boiling-point gasoline, or one or more of these can also be used to elute the pore-forming agent.
[0038] According to any embodiment of the second aspect of the present invention, the extraction can be performed using a Soxhlet extractor.
[0039] For example, the extraction time can be 8 to 12 hours.
[0040] Furthermore, the extraction process also includes screening to obtain functional materials with a particle size of 430~470µm.
[0041] A third aspect of the present invention provides the application of functional materials based on ester structures obtained by the above preparation method, or the above-mentioned functional materials based on ester structures, in the treatment of perfluorinated and polyfluoroalkyl substances in wastewater.
[0042] Perfluorinated and polyfluoroalkyl substances (PFAS) include perfluorooctanoic acid (PFOA) and perfluorosulfonic acid (PFOS). In fact, the materials used for perfluorooctanoic acid (PFOA) are also applicable to perfluorosulfonic acid (PFOS). When applied to perfluorosulfonic acid (PFOS), the adsorption energy and the size of the material are adjusted according to PFOS.
[0043] According to any embodiment of the third aspect of the present invention, the specific method of the application includes: adjusting the pH of the water containing perfluorinated and polyfluoroalkyl substances to 1-5, adding the functional material based on the ester structure, and performing adsorption separation treatment under light-protected conditions.
[0044] It should be noted that the application of the ester-based functional material in the adsorption of perfluorinated and polyfluoroalkyl substances (PFOA) in water involves adjusting the pH of the water containing PFOA and PFOA to 1-5. The adsorption of PFOA and PFOA by the functional material is achieved through charge regulation technology. Specifically, under acidic conditions, PFOA exists in water in molecular form. At this time, electrostatic attraction and hydrogen bonding can occur between the ester groups in the functional material and the carboxyl groups in the PFOA molecules, thereby achieving effective capture of PFOA. Furthermore, the micellar capture principle is utilized; after the functional material adsorbs PFOA, the adsorbed PFOA forms corresponding micellar clusters, thereby increasing the adsorption capacity for PFOA.
[0045] Specifically, the pH of water containing perfluorinated and polyfluoroalkyl substances can be adjusted to 1-2, 1-3, 1-4, or 1-5, for example, pH values of 1, 2, 3, 4, or 5. Preferably, the pH value is adjusted to 1.
[0046] According to any embodiment of the third aspect of the present invention, the pH value of water containing perfluorinated and polyfluoroalkyl substances is adjusted by an acid solution, wherein the acid solution may be hydrochloric acid or sulfuric acid, preferably hydrochloric acid.
[0047] According to any embodiment of the third aspect of the present invention, the concentration of perfluorinated and polyfluoroalkyl substances in the water body is 40~280 mg / L.
[0048] According to any embodiment of the third aspect of the present invention, the adsorption treatment time is 3-5 hours.
[0049] According to any embodiment of the third aspect of the present invention, the temperature of the adsorption treatment is room temperature, which can be 25~26°C.
[0050] For example, adsorption can be carried out at room temperature (25°C).
[0051] According to any embodiment of the third aspect of the present invention, the dosage of the functional material based on the ester structure is 0.05~0.2g / 150mL.
[0052] According to any embodiment of the third aspect of the present invention, the perfluorinated and polyfluoroalkyl substances include perfluoroalkyl substances, and the perfluoroalkyl substances include perfluorosulfonic acids and perfluorocarboxylic acids.
[0053] Preferably, the perfluoroalkyl substance is a perfluorocarboxylic acid with a chain length of C4 to C14; more preferably, the perfluorocarboxylic acid is perfluorooctanoic acid (PFOA).
[0054] The perfluorosulfonic acid is perfluorosulfonic acid (PFOS).
[0055] According to a fourth aspect of the present invention, a method for regenerating the functional material based on the ester structure is also disclosed, specifically comprising: after adsorption treatment, separating the adsorbed functional material based on the ester structure by solid-liquid separation, and regenerating the adsorbed functional material by desorption with an eluent.
[0056] According to any aspect of the regeneration method of the fourth aspect of the present invention, the solid-liquid separation may be filtration separation.
[0057] According to any aspect of the fourth aspect of the present invention, the regeneration method comprises water as the eluent, preferably water.
[0058] 3. Beneficial effects Compared with the prior art, the beneficial effects of the present invention are as follows: I. Functional materials based on ester group structure: (1) The functional material based on ester structure provided by the present invention starts from the perspective of the charge regulation effect between the monomers and crosslinking agents in the reactants and PFOA. Through the interaction between PFOA and functional materials, monomers and crosslinking agents are selected in a targeted manner to prepare a new type of functional material with good adsorption and separation effect on PFOA. (2) The functional material based on ester structure provided by the present invention uses a pore-forming agent to design a pore structure with an average pore size of 2~10nm and a pore size concentrated in 3~5nm, so as to form a pore channel with perfluoroalkyl substances and achieve better PFOA capture effect. (3) The functional material based on ester structure provided by the present invention has strong electrostatic interaction between the polymer and PFOA in acidic environment and reversible dissociation in non-acidic conditions. The pH value of the system can be adjusted by washing with water to change the form of PFOA, thereby weakening the interaction with the adsorbent and promoting the green regeneration of the adsorbent. I. Applications of functional materials based on ester group structures: (1) In the application of the functional material based on ester structure provided by the present invention in the adsorption of perfluorinated and polyfluoroalkyl substances in water, after adjusting the pH of the water containing perfluorinated and polyfluoroalkyl substances to 1~5, the functional material has a high adsorption capacity for PFAS in the water. This is due to the micelle capture mechanism, that is, after the functional material adsorbs PFAS, the adsorbed PFAS will form corresponding micelle clusters on the functional material, thereby improving the adsorption capacity for PFAS. Since it matches the molecular structure of pollutants, the functional material is particularly suitable for the efficient enrichment and green regeneration of perfluorooctanoic acid (PFOA). (2) The pore size of the novel functional material based on the ester structure provided by this invention is concentrated in the range of 3-5 nm, which can be adapted to form pores with perfluoroalkyl substances, thus enabling better adsorption; moreover, the specific surface area of this functional material is relatively high, ranging from 440.5 to 510.5 nm. 2 / g, giving it good adsorption capacity; (3) The functional material based on ester structure provided by the present invention can be repeatedly desorbed and regenerated, which is convenient for recycling. After desorption and regeneration, it still has good adsorption capacity, and the regenerated material has almost no effect on the adsorption capacity. Moreover, after adsorption saturation, water can be used as an eluent to achieve desorption and regeneration. Compared with traditional ion exchange resins, which require salt or organic solvents to complete the desorption process after adsorption saturation, this invention avoids the secondary pollution problem caused by using salt or organic solvents and realizes the green regeneration of novel functional materials based on ester structure. Attached Figure Description
[0059] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. However, it should be understood that these drawings are designed for illustrative purposes only and are not intended to limit the scope of the present invention. Furthermore, unless specifically indicated, these drawings are intended only to conceptually illustrate the structural construction described herein and are not necessarily drawn to scale.
[0060] Figure 1 The image shows a physical sample of the functional material based on the ester structure synthesized in Example 1 of this invention. Figure 2 This is a pore size and pore volume distribution diagram of the ester-based functional material synthesized in Example 1 of the present invention. In the diagram, the horizontal axis represents the pore size and the vertical axis represents the pore volume. Figure 3 The figure shows the adsorption isotherm of the ester-based functional material synthesized in Example 1 of the present invention at pH=1. In the figure, the horizontal axis represents the solute concentration and the vertical axis represents the equilibrium adsorption amount of solute. Figure 4 This is a pore size distribution diagram of the ester-based functional material synthesized in Example 2 of the present invention; Figure 5 This is a pore size distribution diagram of the ester-based functional material synthesized in Example 3 of the present invention; Figure 6 AR-1 represents the removal rate of perfluorooctanoic acid (PFOA) by the ester-based functional materials synthesized in Examples 1-3 of this invention at pH=1. AR-2 represents the functional material synthesized in Example 1, AR-2 represents the functional material synthesized in Example 2, and AR-3 represents the functional material synthesized in Example 3. Figure 7 The adsorption isotherm of the ester-based functional material synthesized in Comparative Example 1 of this invention at pH=1. Figure 8 The adsorption isotherm of the ester-based functional material synthesized in Comparative Example 2 of this invention at pH=1. Figure 9 The graph shows the removal rate of perfluorooctanoic acid at different pH values in Application Examples 1-5. In the graph, the horizontal axis represents the pH value and the vertical axis represents the removal rate. Figure 10 This is a diagram showing the electrostatic potential between ester-based functional materials and PFOA. Figure 11 The state of the system before PFOA adsorption in functional materials based on ester groups; Figure 12 The state of the system after PFOA adsorption in functional materials based on ester groups; Figure 13 This is a graph showing the interaction trends between structural units containing -CO-O- groups and PFOA. Figure 14 The results show the molecular geometry optimization of structural units containing -CO-O- groups and PFOA; Figure 15 To obtain a molecular model of PFOA through molecular configuration optimization; Figure 16 The results are simulations of the adsorption behavior of three models composed of -CO-O- structural units with D=2 nm, 4 nm, and 8 nm. Figure 17 The figure shows the system state of micelles formed after PFOA adsorption by a material with a pore size of D=4nm. In the figure, the horizontal axis represents size and the vertical axis represents intensity. Figure 18 This refers to a local structural unit of the functional material prepared in Example 1; Figure 19 The image shows a scanning electron microscope (SEM) image of the functional material prepared in Example 1. Figure 20 The graph shows the cyclic adsorption performance of the functional material prepared in Example 1. In the graph, the horizontal axis represents the number of cycles, and the vertical axis represents the concentration of PFOA. Detailed Implementation
[0061] This disclosure can be more readily understood by referring to the following description in conjunction with examples, all of which form part of this disclosure. It should be understood that this disclosure is not limited to the specific products, methods, conditions, or parameters described and / or illustrated herein. Furthermore, the terminology used herein is for the purpose of describing particular embodiments by way of example only and is not intended to be limiting, unless otherwise stated.
[0062] It should also be understood that, for clarity, certain features of this disclosure may be described herein in the context of individual embodiments, but may also be provided in combination with each other in individual embodiments. That is, unless obviously incompatible or specifically excluded, each individual embodiment is considered to be combinable with any other embodiment, and such combination is considered to represent another different embodiment. Conversely, for brevity, various features of this disclosure described in the context of individual embodiments may also be provided individually or in any sub-combination. Finally, while a particular embodiment may be described as part of a series of steps or part of a more general structure, each step or substructure may also be considered an independent embodiment in itself.
[0063] Unless otherwise stated, it should be understood that each individual element in the list and each combination of individual elements in the list will be interpreted as a different embodiment.
[0064] In this disclosure, the singular forms of the articles “a,” “one,” and “the” also include the corresponding plural references, and references to a particular value include at least that particular value, unless the context clearly indicates otherwise. Thus, for example, a reference to “substance” is a reference to at least one of such substance and its equivalents.
[0065] When an item is described using the combined terms “...and / or ...", the description should be understood to include any one of the listed items and all combinations thereof.
[0066] Generally, the use of the term "about" indicates an approximation that can vary depending on the desired characteristics obtained from the disclosed subject matter and will be interpreted in a context-dependent manner based on function. Therefore, those skilled in the art will be able to interpret a degree of difference on a case-by-case basis. In some cases, the number of significant figures used when expressing a particular value can be a representative technique for determining the difference allowed by the term "about." In other cases, a gradient within a range of values can be used to determine the range of differences allowed by the term "about." Furthermore, all ranges in this disclosure are inclusive and composable, and references to values within a range include every value within that range.
[0067] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terms used herein and / or include any and all combinations of one or more of the associated listed items.
[0068] Unless otherwise specified in the following examples, the conditions were performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0069] The present invention will be further illustrated below with reference to specific embodiments, but these embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in this technical field. The essential features and significant effects of the present invention can be seen from the following embodiments. The described embodiments are some, but not all, embodiments of the present invention, and therefore do not limit the present invention in any way. Any non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are within the protection scope of the present invention.
[0070] This invention provides a functional material based on an ester structure. The design principle of this functional material is based on a precise design strategy guided by multi-scale theoretical calculations. (1) Use density functional theory (DFT) to screen monomers with PFOA recognition function and establish intermolecular interaction maps; (2) Molecular dynamics (MD) simulation was used to optimize the topology of the three-dimensional interpenetrating network to achieve precise matching between the pore size distribution and the PFOA size; (3) A pH-responsive molecular transformation mechanism was introduced to construct a smart adsorption interface with reversible group conversion.
[0071] This hierarchical design concept breaks through the static action mode of traditional adsorbents: in the acid capture stage, specific recognition of PFOA molecules is achieved through electrostatic-multiple hydrogen bonding-hydrophobic interactions and the size matching effect of pore structure; in the regeneration stage, the spatial configuration of functional groups is regulated by pH-responsive electrostatic attraction, achieving green regeneration through in-situ reconstruction of the adsorption interface. By establishing a full-chain mechanism of "molecular recognition-mass transfer enhancement-interface regulation," this study not only provides an innovative solution for the deep purification of ultra-trace PFOA in complex environmental systems, but also establishes a theoretical framework for the rational design of environmental functional materials through thermodynamic-kinetic synergistic optimization.
[0072] (1) Interaction between PFAS and -CO-O- Perfluorinated and polyfluoroalkyl substances (PFAS) include perfluorosulfonic acid compounds and perfluorocarboxylic acid compounds, typically, for example, perfluorooctanoic acid (PFOA). The hydrophobic CF chain and hydrophilic carboxyl (-COOH) group of PFOA give it amphiphilic properties. PFOA mainly exists in molecular form in electroplating wastewater. In molecular PFOA, the -COOH group helps to form hydrogen bonds and electrostatic interactions. The interaction between the adsorbent and PFOA must be carefully considered when designing adsorbents.
[0073] Yang's research shows that (Yang, WB et al. Adsorption of surfactants ontoacrylic ester resins with different pore size distribution. Sci. China Ser. B (49, 445–453 (2006)) Polymer adsorbents containing ester groups (-CO-O-) effectively capture sodium dodecyl sulfate through hydrophobic and hydrogen bonding interactions. Given the similar amphiphilicity of PFOA and sodium dodecyl sulfate, we hypothesize that adsorbents with -CO-O- groups may also exhibit good adsorption performance for PFOA.
[0074] While considering hydrophobic interactions, it is also necessary to integrate multiple mechanisms into the adsorbent design concept to enhance PFOA capture.
[0075] This application establishes structural units containing -CO-O- groups and reveals the interaction trend between structural units containing -CO-O- groups and PFOA through frontier molecular orbital theory. Figure 13 The highest occupied molecular orbital (HOMO) of the -CO-O- group and the lowest unoccupied molecular orbital (LUMO) of PFOA exhibit energy level matching characteristics, confirming that they can form a stable complex through electron donor-acceptor interactions. Further analysis using electrostatic potential ( Figure 10 Analysis verified this mechanism: under acidic conditions, the negative potential region of the -CO-O- group and the positive potential center of the -COOH group of protonated PFOA generate a strong electrostatic attraction, and the electrostatic potential difference between the two drives electrostatic complexation. Molecular geometry optimization results show that ( Figure 15 The structural units containing -CO-O- groups have double hydrogen bonds with PFOA: (i) the carbonyl oxygen (OH distance 1.61 Å) forms a main hydrogen bond with the H of protonated PFOA; (ii) the β-H in the structural monomer forms a weak hydrogen bond with the F of PFOA (FH distance 2.45 Å), which synergistically enhances the adsorption stability.
[0076] The above Figure 10-15 This indicates that the -CO-O- group can form a stable adsorption relationship with PFAS such as PFOA.
[0077] (2) Pore size of functional materials Studies have shown that the pore size distribution of adsorbents significantly affects the adsorption efficiency of pollutants: when the pore size of the adsorbent is approximately four times that of the target pollutant (Yang, WB et al. Adsorption of surfactants onto acrylicester resins with different pore size distribution). Sci. China Ser. B 49, 445–453 (2006) (with optimal adsorption performance at D / d≈4), showing the best capture effect. Therefore, the molecular size of PFOA should be considered in adsorbent design, and adsorbents with appropriate pore sizes should be developed accordingly to effectively capture PFOA.
[0078] Through molecular configuration optimization, the longitudinal molecular size of PFOA was found to be approximately 1.1 nm. Figure 14 Based on the previously discovered four-fold ratio between pore size (D) and pollutant size (d) and adsorption efficiency, and combining the classical Kelvin equation and Gibbs adsorption theory, a confined space mass transfer model was established using molecular dynamics (MD). This model demonstrates that when the pore size matches the PFOA size, PFOA micelles are formed after adsorption, and the fluorine-fluorine interactions and intermolecular hydrogen bonds within the micelles produce a synergistic enhancement effect. This model provides a theoretical basis for constructing a three-dimensional interpenetrating network topology, and the system exhibits a breakthrough dual-effect synergy. To verify this hypothesis, three models composed of -CO-O- structural units with D=2 nm, 4 nm, and 8 nm were constructed using MD simulations, and their adsorption behavior differences were quantified. The simulation results are as follows: Figure 16 As shown, pore sizes ranging from 2 to 8 nm all exhibit a certain adsorption capacity for pollutants, and different pore sizes significantly regulate the adsorption kinetics. (i) D=2 nm system: The confined space leads to the concentration of the main adsorption sites at the pore opening and the short average residence time, indicating that there is a significant orientation constraint; (ii) D=4 nm system: Micellar assembly phenomenon was observed. The intermolecular fluorine-fluorine interaction and pore wall stacking formed a dual synergistic effect, achieving the goal of effectively capturing PFOA; (iii) D=8 nm system: The adsorbed molecules are discretely distributed, the desorption frequency increases, and the pore size is too large, which causes some adsorbed PFOA molecules to fail to fully occupy the space inside the pore, and the remaining molecules escape, thereby reducing the overall retention efficiency.
[0079] Based on this, this study designed and synthesized pore size gradient materials with average pore sizes of 2.1 nm, 4.3 nm, and 8.2 nm.
[0080] (3) Desorption method design MD further revealed the adsorption / desorption mechanism from an energy perspective: in an acidic environment, the stable conformation of the composite system between the material and the pollutant showed an adsorption energy as low as -4310.92 kcal / mol. Figure 12 ), significantly lower than under neutral conditions -948.73 kcal / mol ( Figure 11 The sharp decrease in adsorption energy can be attributed to the strong electrostatic interaction between the polymer and PFOA under acidic conditions. Notably, the non-covalent bonds formed by protonation undergo reversible dissociation under non-acidic conditions, providing a theoretical basis for the green regeneration of the adsorbent: when the system returns to a neutral state, the adsorbate-adsorbent interaction weakens significantly, indicating that green regeneration can be achieved through simple water washing after adsorption saturation. Therefore, a pH-responsive molecular form transformation mechanism can be established to complete the material regeneration cycle. During desorption, simple water washing can adjust the pH of the system, thereby changing the form of PFOA and weakening its interaction with the adsorbent, promoting the green regeneration of the adsorbent.
[0081] (4) Test method: The theoretical calculation design process includes: Quantum Chemistry: Molecular geometry was optimized using density functional theory (DFT). Geometry optimization was performed at the B3LYP functional level using the 6-311G(d,p) basis set, and frequency calculations confirmed the optimized structure had no imaginary frequencies (spin multiplicity set to 1). All calculations employed an integral equation-based polarized continuum model (IEFPCM) to account for water-soluble effects and utilized dispersion correction (DFT-D3).
[0082] Molecular Dynamics Simulations: Classical molecular dynamics (CMD) simulations were performed using molecular dynamics simulation software. After structural optimization at the B3LYP / 6-31G(d,p) level, GAFF force field parameters were obtained. A simulation box containing tubular resin was constructed using gmx genconfig, and water molecules and perfluorooctanoic acid (PFOA) were introduced into the system using the gmx insert-molecules method. After energy minimization, a 15-nanosecond NVT ensemble simulation was performed. Model visualization software was used to achieve model visualization, and the V-rescale temperature coupling method was applied to maintain thermodynamic equilibrium. Post-processing and statistical analysis of all CMD data were performed using Python scripts and the molecular dynamics analysis module. The target molecular structure was constructed using the Visualization module, followed by geometry and energy optimization using the Dmol3 module. Optimization parameters were set as follows: task type (Geometry Optimization and Energy), precision level (Fine), functional type (GGA-PBE), and basis set type (DND). The optimized polymer molecules were imported into the Amorphous Cell module to construct an acellular model, generating perfluorooctanoic acid (PFOA) simulation systems with and without hydrochloric acid. After completing the model construction using the build layer function, molecular dynamics optimization was performed in the Forcite module, with parameters set as follows: task type (Dynamics), accuracy level (Fine), and force field type (COMPASSII).
[0083] The adsorption effect was characterized based on the isothermal adsorption curve, specifically including the following steps: Prepare a solution with a pH of 1 and a concentration range of 40-280 mg / L. -1 PFOA aqueous solution was prepared by adding 50 mg of adsorbent (PFOA) to 150 mL of the target solution and shaking for 48 hours. All experiments were conducted at 25 °C with a stirring rate of 150 rpm. The PFOA concentration was measured, and the adsorption data were fitted and analyzed using the Langmuir isotherm adsorption model.
[0084] [Aperture] and [Specific Surface Area]: Specific surface area and porosity analysis were performed using a Micromeritics ASAP 2460 fully automated specific surface area and porosity analyzer. Before testing, all samples were degassed for 24 hours under dynamic vacuum at 120℃. Nitrogen adsorption-desorption isotherms were measured at liquid nitrogen temperature (77 K). Specific surface area was calculated using the Brunauer-Emmett-Teller (BET) method, and pore size distribution was analyzed using the Barret-Joyner-Halenda (BJH) method.
[0085] Example 1 This embodiment discloses a method for preparing functional materials based on ester groups, which is synthesized using suspension polymerization and includes the following steps: The monomer, crosslinking agent, porogen, and aqueous phase containing dispersant are polymerized under the action of an initiator to obtain the functional material based on the ester structure.
[0086] Specifically, the following steps are included: S1. Under continuous stirring, a pore-forming agent and an initiator are added to the monomer and crosslinking agent; S2. Reaction: The mixture obtained in step S1 is added to a medium containing a dispersant and subjected to a constant-temperature polymerization reaction. The mixture is kept at this temperature to obtain the functional material based on the ester structure. The polymerization reaction is carried out in a 1000 mL three-necked flask. The aqueous phase is stirred for 30 minutes under nitrogen purging before the reactants (i.e., monomers and crosslinking agents), porogens and initiators are added. The stirring speed is 300 rpm and the polymerization reaction temperature is 85°C. After reacting for 8 hours, the mixture is kept at 90°C for 10 hours. Specifically, the proportions of each raw material are as follows: The aqueous phase contains 150g of water, with 0.15g of hydroxyethyl cellulose added as a dispersant. The reactants contain 8.5g of methyl methacrylate monomer, 42.5g of trimethylolpropane trimethyl methacrylate crosslinking agent, and 17g of dodecylbenzene porogen. Benzoyl peroxide is also added as an initiator. Before use, both the reactants and the aqueous phase containing the porogen and initiator are pre-purged with nitrogen for 5 minutes to remove oxygen from the solution.
[0087] S3. Purification: After cooling, the material is extracted with acetone using a Soxhlet extractor for 10 hours, then sieved through 18-mesh and 46-mesh sieves to obtain the target substance, namely the functional material based on the ester group structure. Figure 1 As shown in the bottle.
[0088] Combination Figure 2 The pore size and pore volume distribution maps obtained from BET testing show that the pore size of the prepared ester-based functional material is concentrated in the range of 3-4 nm, with an average pore size of 4.0 nm and a specific surface area of 450.6 m². 2 / g.
[0089] Combination Figure 3 The results showed that the synthesized ester-based functional material exhibited a significant adsorption effect on PFOA, with an adsorption capacity (saturated adsorption capacity) of approximately 544 mg·g⁻¹ at pH=1. -1The ester groups in the functional material undergo protonation with the target pollutant PFOA under acidic conditions, thus leading to adsorption. A good matching effect is formed between the PFOA molecular size and the pore size of the synthesized functional material, further confirming the excellent adsorption effect of the synthesized functional material on PFOA.
[0090] Example 2 The functional material based on the ester structure was synthesized by suspension polymerization. The difference between it and Example 1 is that 17g of trimethylolpropane trimethacrylate (TMT) was added as a crosslinking agent, 2.6g of dodecylbenzene was added as a pore-forming agent, and 1.3g of benzoyl peroxide was added as an initiator to the reactants.
[0091] The polymerization reaction temperature was 80℃, and after 6 hours of reaction, it was held at 85℃ for 8 hours. The pore size of the resulting functional material is as follows: Figure 4 As shown, the average particle size is approximately 2.3 nm. Figure 6 As can be seen, the functional material with an average pore size of 4 nm in Example 1 has higher adsorption performance and a better capture effect on perfluorooctanoic acid than the functional material with an average pore size of about 2.3 nm.
[0092] Example 3 The functional material based on the ester structure was synthesized by suspension polymerization. The difference between it and Example 1 is that 68g of trimethylolpropane trimethacrylate was added as a crosslinking agent, 15.3g of dodecylbenzene was added as a pore-forming agent, and 3.8g of benzoyl peroxide was added as an initiator to the reactants.
[0093] The polymerization reaction temperature was 90℃, and after reacting for 10 hours, the mixture was held at 95℃ for 12 hours. The pore size of the resulting functional material is as follows: Figure 5 As shown, the average particle size is approximately 9.4 nm. Figure 6 As can be seen, the functional material with an average pore size of 4 nm in Example 1 has higher adsorption performance and a better capture effect on perfluorooctanoic acid than the functional material with an average pore size of about 9.4 nm.
[0094] Comparative Example 1 This comparative example provides a functional material prepared using a process essentially the same as in Example 1, except that 5g of xylene was used as the pore-forming agent. An ester-based functional material with an average pore size of approximately 2nm was obtained. Isothermal adsorption curves were then tested using this material under the same conditions as in Example 1, and the results are shown below. Figure 7 Therefore, it can be seen that the functional material in Example 1 with a pore size of about 4 nm has higher adsorption performance and a higher capture effect on perfluorooctanoic acid than the functional material with an average pore size of about 1 nm.
[0095] Comparative Example 2 This comparative example provides a functional material prepared using a process essentially the same as in Example 1, except that 10g of xylene was used as the pore-forming agent. An ester-based functional material with an average pore size of approximately 8nm was prepared. Isothermal adsorption curves were then performed using this material under the same conditions as in Example 1. The results are shown in [link to example]. Figure 8 Therefore, it can be seen that the functional material in Example 1 has an average pore size of about 4 nm, and its capture effect on perfluorooctanoic acid is higher than that of the functional material with an average pore size of about 11 nm.
[0096] Application Example 1 The application method of the novel functional material based on the ester group structure prepared in Example 1 for adsorbing perfluorooctanoic acid (PFOA) in water is as follows: 150 mL of an aqueous solution containing 240 mg / L PFOA was adjusted to pH 5 with hydrochloric acid, and then 0.1 g of the novel functional material based on the ester group structure was added. The water was placed in a shaker at room temperature and protected from light for 4 hours of adsorption by shaking at a speed of 150 r / min. After the adsorption was completed, the PFOA concentration was detected. The specific results are shown in [link to results]. Figure 9 .
[0097] Application Example 2 The difference from Application Example 1 is that the pH value was adjusted to 4; see the results below. Figure 9 .
[0098] Application Example 3 The difference from Application Example 1 is that the pH value was adjusted to 3; see the results below. Figure 9 .
[0099] Application Example 4 The difference from Application Example 1 is that the pH value was adjusted to 2; see the results below. Figure 9 .
[0100] Application Example 5 The difference from Application Example 1 is that the pH value was adjusted to 1; see the results below. Figure 9 .
[0101] Application Example 6 The functional material adsorbed with perfluorooctanoic acid in Application Example 5 was dispersed in deionized water as an eluent and shaken for 4 hours to desorb and regenerate the functional material. The functional material after desorption can be reused. The functional material desorbed according to the above method was subjected to secondary adsorption according to the adsorption process of Application Example 5. Adsorption was carried out under the same conditions with the newly added 240 mg / L perfluorooctanoic acid solution. The solution after adsorption was tested and found that the adsorption capacity was 95% of the primary adsorption capacity.
[0102] Combination Figure 9It can be clearly observed that as the pH value decreases, the adsorption capacity of the synthesized novel functional material based on the ester structure for perfluorooctanoic acid gradually increases. Based on the experimental results, it can be concluded that the synthesized novel functional material based on the ester structure has good adsorption performance for perfluorooctanoic acid. The reasons are as follows: (1) As the pH value decreases, most of the perfluorooctanoic acid exists in the aqueous solution in molecular form, and some exists in the water environment in ionic form. As the pH value decreases, the carbonyl and ester functional groups contained in the novel functional material system based on the ester structure effectively adsorb perfluorooctanoic acid due to electrostatic interaction under acidic conditions. (2) Under strong acidic conditions, perfluorooctanoic acid exists in molecular form and is adsorbed into the novel functional material with the ester structure through van der Waals forces. (3) Due to the decrease in pH value, during the adsorption process, the adsorbed molecular perfluorooctanoic acid forms a micelle mechanism and is further enriched and removed.
[0103] Combination Figure 10 As shown in the figure, the possible interaction sites between some structural units in the novel functional material and PFOA were analyzed using DFT theory. Based on the electrostatic potential diagram (ESP) analysis of the interaction sites between the material and PFOA, it was found that the two promote adsorption and enhance the complexation between the ester group and PFOA through electrostatic interaction, thereby achieving the separation of perfluorooctanoic acid (PFOA) from water using charge regulation technology.
[0104] Combination Figure 11 and Figure 12 By using molecular dynamics simulation to study the micellar adsorption mechanism of PFOA by ester-based functional materials under acidic conditions, it can be seen that the adsorbed perfluorooctanoic acid forms micelles, demonstrating the effectiveness of micellar capture. Figure 11 The diagram shows the state of the system before adsorption. The upper part shows PFOA dispersed in the solution environment before adsorption, and the lower part shows some structural units of a novel functional material based on an ester group structure. Figure 12 This demonstrates the phenomenon of PFOA forming micelles on the adsorbent surface after adsorption. Through... Figure 11 and Figure 12 This study demonstrates the micellar trapping effect of novel functional materials based on ester structures on perfluorooctanoic acid (PFOA). In Example 1, the micelles formed after the functional material with an average pore size of 4 nm adsorbed PFOA were measured using a Malvern particle size analyzer. Figure 17 This indicates that micelles were formed.
[0105] The functional material prepared in Example 1 was recycled after being washed and regenerated. Experiments showed that the regenerated functional material still maintained a high adsorption efficiency for PFOA, and after 5 cycles of regeneration, the adsorption performance did not decrease significantly. Figure 20 As shown, the functional material prepared in this application has extremely high cycle stability and can be greenly recycled.
[0106] The above description is merely a preferred embodiment of this application and an explanation of the technical principles used. Those skilled in the art should understand that the scope involved in this application is not limited to the technical solutions formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept. For example, technical solutions formed by replacing the above-mentioned features with technical features with similar functions disclosed in this application (but not limited to) each other.
[0107] Apart from the technical features described in the specification, the other technical features are known to those skilled in the art. To highlight the innovative features of this invention, the other technical features will not be described in detail here.
Claims
1. An application of a functional material based on an ester group structure in the treatment of PFOA in wastewater, characterized in that, The functional material has hydrophobic alkyl chains and functional groups containing ester structures; The adsorption energy between the functional group and PFOA is -14.6 kcal / mol to -10.2 kcal / mol; The functional material comprises repeating units formed by methyl methacrylate and a crosslinking agent linked together; The crosslinking agent includes one or both of ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate. The functional material satisfies: The adsorption energy in acidic environments is -4500.5 kcal / mol to -4000.2 kcal / mol; The adsorption energy in a neutral environment is -1000.8 kcal / mol to -900.7 kcal / mol; The functional material is regenerated after being eluted with an eluent, wherein the eluent is water.
2. The application according to claim 1, characterized in that, The ratio of the pore size of the functional material to the size of the PFOA is (2~8):1; and / or, The average pore size of the functional material is 2~10 nm.
3. The application according to any one of claims 1-2, characterized in that, The functional material is obtained by polymerization of methyl methacrylate as a monomer.
4. The application according to any one of claims 1-2, characterized in that, The preparation method of the functional material includes raw materials: monomer, crosslinking agent, initiator and porogen; Including the following steps: The monomer, crosslinking agent, porogen, and medium containing dispersant are polymerized under the action of an initiator, and then subjected to heat preservation to obtain the functional material. The monomer is methyl methacrylate, and the porogen includes dodecylbenzene.
5. The application according to claim 4, characterized in that, The initiator includes one or more of benzoyl peroxide and azobisisobutyronitrile; and / or The dispersant includes hydroxyethyl cellulose; and / or, The medium is water.
6. The application according to claim 5, characterized in that: The weight ratio of the monomer to the crosslinking agent is 1:2 to 1:8, and / or; The weight ratio of the porogen to the sum of the weights of the monomers and crosslinking agents in the reactants is 1:3 to 1:10; and / or, The weight ratio of the initiator to the sum of the weights of the monomers and crosslinking agents in the reactants is 1:100 to 6:100; and / or, The weight ratio of the dispersant to the medium is 0.5:1000 to 5:1000.
7. The application according to claim 4, characterized in that: The polymerization reaction is carried out at a temperature of 80-90℃ for 6-10 hours. The insulation temperature is 85~95℃, and the insulation time is 8~12h.
Citation Information
Patent Citations
High-specific-surface acrylates adsorption resin and synthesizing method
CN1814632A